2016
DOI: 10.7883/yoken.jjid.2015.028
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Implication of Computed Tomography Images of Chronic Pulmonary Aspergillosis

Abstract: SUMMARY: Chronic pulmonary aspergillosis (CPA) is a refractory disorder that needs long-term antifungal treatment and occasionally results in fatal respiratory failure and hemoptysis. However, the pathological features of the disorder have not been thoroughly delineated. Thirty cases were therefore analyzed clinically and histologically to elucidate the pathophysiology of CPA. The subjects comprised 14 individuals who underwent surgical removal and 16 patients who died. No subject exhibited a severely immunoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
0
5
0
2
Order By: Relevance
“…Active movement and rubbing against the cavity wall of an immature and fragile fungus ball might have led to reduction in its size, along with conversion to an invasive form in some portions of the fungus ball. This assumption was supported by a research on pathology, which showed that a fungus ball is fragile and may be broken easily into fragments; also, the cavity and connecting bronchi were observed to be filled by massive inflammatory exudates and necrotic tissues (20).…”
Section: Discussionmentioning
confidence: 86%
“…Active movement and rubbing against the cavity wall of an immature and fragile fungus ball might have led to reduction in its size, along with conversion to an invasive form in some portions of the fungus ball. This assumption was supported by a research on pathology, which showed that a fungus ball is fragile and may be broken easily into fragments; also, the cavity and connecting bronchi were observed to be filled by massive inflammatory exudates and necrotic tissues (20).…”
Section: Discussionmentioning
confidence: 86%
“…In our CPA patients, specific chest CT findings, like halo sign and air crescent sign, were rarely seen. The rate of pulmonary cavitation (11.90%) is much lower than reported (26, 94.2%) [15, 21]. These 42 CPA patients come from our hospital and only 3 patients have previous tuberculosis.…”
Section: Discussionmentioning
confidence: 69%
“…Imaging findings in patients with CPA consist mainly of cavities, fungus balls, pleural thickening and pericavitary consolidation in the upper lobes [4,5]. The treatment of pulmonary aspergillosis diseases is usually conservative management and pharmacotherapy in the form of azole antifungal agents.…”
Section: Discussionmentioning
confidence: 99%